The effects of organizational trust and empowering leadership on group conflict: Psychological safety as a mediator - Baekkyoo Joo; So Kyum Yoon; Diane Galbraith (Organization Management Journal (OMJ), 2023)
Purpose - In a knowledge-based economy, employees' perception of psychological safety in their wok unit is critical for group conflict. The purpose of this study is to investigate the mediating role of psychological safety between the predictors (i.e. organizational trust and empowering leadership) and the outcome variable, group conflict. Design/methodology/approach - Data was drawn from 633 employees from a global automobile company headquartered in South Korea. Construct validity of the measurement model was examined using a confirmatory factor analysis. The hypothesized model was tested by a structural equation modeling and the bootstrap analysis. Findings - Organizational trust and empowering leadership accounted for 68% of the variance in employees' psychological safety. The three antecedents (i.e. organizational trust, empowering leadership and psychological safety) explained 20% of the variance in group conflicts. Psychological safety significantly and fully mediated the relationship between organizational trust and group conflict and the relationship between empowering leadership and group conflict. Practical implications - Human resources and organization development professionals can help employees feel more psychologically safe in an organization by developing empowering leaders and making more trustworthy organizational culture. When employees perceive a high level of psychological safety, they are likely to feel less conflict in their team. Originality/value - This study examined the antecedents and consequences of psychological safety of knowledge workers in a non-Western cultural context. Psychological safety played a pivotal role as a mediator. To the best of the authors' knowledge, this is the first study that empirically found the direct link between organizational trust and psychological safety and the relationship between empowerment leadership and psychological safety.
Keywords: 650; Empowering leadership; Group conflict; Organizational trust; Psychological safety; South Korea